Um sistema de storytelling textual para gerar histórias que despertem surpresa, suspense e curiosidade - Albuquerque, Alexandre Cordeiro de (2011)
Writing stories that please a target audience is not an easy task for their authors. The creation of stories by a computer system that are able to entertain and catch the reader s attention is an even more complex task. This work details a computer solution that produces structured narratives to arouse three cognitive feelings on readers: suspense, surprise and curiosity. To achieve this goal, the concepts of the Structural-Affect Theory of Stories were used. This theory states that these emotions might be evoked through the manipulation of the event order of a narrative plot.